Effect of wrist dorsiflexion on ultrasound-guided radial artery catheterisation using dynamic needle tip positioning technique in adult patients: a randomised controlled clinical trial. Issue 7 (26th January 2021) - Xiao, Qingyu; Xu, Dejiang; Zhuang, Shaohui
Abstract : Background: It is generally recommended to keep the wrist joint mildly dorsiflexed during radial artery catheterisation. However, wrist dorsiflexion might decrease the success rate of radial artery catheterisation with dynamic needle tip positioning technique. Therefore, we assessed the success rates of two groups with or without wrist dorsiflexion by 5 cm wrist elevation in adult patients. Methods: This randomised controlled clinical trial was performed between March and December 2018 in the First Affiliated Hospital of Shantou University Medical College, China. We recruited 120 adult patients undergoing major surgical procedures and randomly allocated them into two groups: dorsiflexion group (group D) and neutral group (group N). The primary outcome was first-attempt success rates of two groups. Secondary outcomes were overall success rates within 5 min; numbers of insertion and cannulation attempts; overall catheterisation time; duration of localisation, insertion and cannulation; and complication rates of catheterisation. Results: First-attempt success rate was 88.3% in group D and 81.7% in group N (p=0.444). The overall success rate within 5 min was 93.3% in group D compared with 90.0% in group N (p=0.743). Numbers of insertion and cannulation attempts, overall catheterisation time, duration of localisation and insertion, and complication rates did not show a significant difference between the two groups. Cannulation time was longer in group N (35.68 s) than that in group D (26.19 s; p<0.05). Conclusion: Wrist dorsiflexion may not be a necessity for ultrasound-guided radial artery catheterisation using dynamic needle tip positioning technique in adult patients. Trial registration number: ChiCTR1800015262.